Pseudomonas leptonychotis sp. nov., isolated from Weddell seals in Antarctica - Nováková, Dana; Švec, Pavel; Zeman, Michal; Busse, Hans-Jürgen; Mašlaňová, Ivana; Pantůček, Roman; Králová, Stanislava; Krištofová, Lucie; Sedláček, Ivo (International journal of systematic and evolutionary microbiology, 2020)
A taxonomic study was carried out on four Gram-stain-negative strains P5773T, P6169, P4708 and P6245, isolated from anus or mouth samples of Weddell seals at James Ross Island, Antarctica. The results of initial 16S rRNA gene sequence analysis showed that all four strains formed a group placed in the genus Pseudomonas and found Pseudomonas guineae and Pseudomonas peli to be their closest neighbours with 99.9 and 99.2 % sequence similarity, respectively. Sequence analysis of rpoD, rpoB and gyrB housekeeping genes confirmed the highest similarity of isolates to P. peli (rpoD) and to P. guineae (rpoB and gyrB). The average nucleotide identity value below 86 %, as calculated from the whole-genome sequence data, showed the low genomic relatedness of P5773T to its phylogenetic neighbours. The complete genome of strain P5773T was 4.4 Mb long and contained genes encoding proteins with biotechnological potential. The major fatty acids of the seal isolates were summed feature 8 (C18 : 1ω7c), summed feature 3 (C16 : 1ω7c/C16 : 1ω6c) and C16:0. The major respiratory quinone was Q9. The major polar lipids were phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol. Putrescine and spermidine are predominant in the polyamine pattern. Further characterization performed using repetitive sequence-based PCR fingerprinting and MALDI-TOF MS analysis showed that the studied isolates formed a coherent cluster separated from the remaining Pseudomonas species and confirmed that they represent a novel species within the genus Pseudomonas, for which the name Pseudomonasleptonychotis sp. nov. is suggested. The type strain is P5773T (=CCM 8849T=LMG 30618T).
Keywords: Antarctic Regions; DNA bakterií; Antarktida; Phylogeny; techniky typizace bakterií; Sequence Analysis, DNA; Genes, Bacterial; zastoupení bazí; RNA ribozomální 16S; zvířata; Base Composition; RNA, Ribosomal, 16S; sekvenční analýza DNA; DNA, Bacterial; mastné kyseliny; Phospholipids; fylogeneze; bakteriální geny; Seals, Earless; Ubiquinone; Bacterial Typing Techniques; fosfolipidy; Animals; tuleňovití; ubichinon; Fatty Acids; Pseudomonas